Met een los onderschrift "1903 De jonge proletaar 1909". Uit archief F. Domela Nieuwenhuis, map VI d C, no. 3
Met een los onderschrift "1903 De jonge proletaar 1909". Uit archief F. Domela Nieuwenhuis, map VI d C, no. 3.